Variations of the Saphenopopliteal Junction: An Ultrasonography Study in a Young Population, A Systematic Review and A Meta-Analysis - Veselá, Michaela; Beneš, Michal; Dostálová, Gabriela; Aleš Linhart; Kachlík, David (Angiology, 2024)
Saphenopopliteal junction classification has been developing, but still the precise knowledge of junction type is crucial for proper surgical treatment. We examined the saphenopopliteal junction by duplex venous scanning in 244 extremities in healthy volunteers (median age: 23.0 years, 83 females, 39 male) and performed a meta-analysis of 13 studies focusing on structural types of the junction. According to Schweighoffer's classification we distinguished 5 types of the junction and we subdivided type A according to Cavezzi's classification of gastrocnemial veins termination into two. We added type F (small saphenous vein-SSV terminates into popliteal vein-PV), described especially in cadaveric studies. In our study, the most frequent type was A1 (96 cases), followed by C (70), B (48), A2 (20), E (6), D (3) and F (0). The pooled prevalence estimate for types A + B + D + E was 54.7% (95% CI 40.9-69.6%) and for type C 24.4% (95% CI 19.3-29.5%), whereas in 17.1% (95% CI 6.3-27.9%) of cases, the SSV terminated in the PV with no cranial extension present. The knowledge of the saphenopopliteal junction and its variations prevalence can help clinicians to quickly identify the real type of the junction during routine examination. In mid-European population, the main type is A1 and worldwide type A.
Keywords: Predictive Value of Tests; mladý dospělý; prediktivní hodnota testů; Ultrasonography, Doppler, Duplex; lidé; Female; Popliteal Vein; mužské pohlaví; Saphenous Vein; Male; vena saphena; duplexní dopplerovská ultrasonografie; Young Adult; ženské pohlaví; vena poplitea; Humans